The Unknown Cause of Pott’s Puffy Tumor – Importance of Early Diagnose - Pinheiro, João Páscoa; Santos, Eva; Rato, Joana; Alexandrino, Henrique; Costa, Gonçalo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Pott’s puffy tumor (PPT) is characterized by swelling of the glabelar region and osteomyelitis of the frontal bone, owing to a subperiosteal pseudoinflammatory tumor responsible for the detachment of the pericranium from the outer table of the skull. Nowadays, the incidence of PPT is very low, so this entity is frequently underdiagnosed. The late treatment and identification of PPT are strongly associated with intracranial complications, which could jeopardize the life of the patient.In the literature, PPT is described as a complication of frontal head trauma or of chronic sinusitis. There are a few cases reported in patients with frontal insect bites or in recreational nasal drug users, such as cocaine or methamphetamines.In the present case report, the authors describe the case of a 40-year-old male who was submitted to a frontal sebaceous cyst surgery. In the postoperative period, he developed an infectious process compatible with PPT. After an extensive review of the literature, no similar cases were identified. Therefore, in the opinion of the authors, sebaceous cyst surgery should be included in the short list of risk factors for the development of PPT.
Keywords: epidural abscess; frontal osteomyelitis; Pott puffy tumor; sebaceous cyst